Preparation and in vitro characterization of gellan based floating beads of acetohydroxamic acid for eradication of H. pylori - Rajinikanth, P.S.; Mishra, B. (My University, 2007)
Gellan based floating beads of acetohydroxamic acid (AHA) were prepared by the ionotropic gellation method to achieve controlled and sustained drug release for treatment of Helicobacter pylori infection. The prepared beads were evaluated for diameter, surface morphology and encapsulation efficiency. Formulation parameters like concentrations of gellan, chitosan, calcium carbonate and the drug influenced the in vitro drug release characteristics of beads. Drug and polymer interaction studies were carried out using differential scanning calorimetry. Chitosan coating increased encapsulation efficiency of the beads and reduced the initial burst release of the drug from the beads. Kinetic treatment of the drug release data revealed a matrix diffusion mechanism. Prepared floating beads showed good antimicrobial activity (in vitro H. pylori culture) as potent urease inhibitors. In conclusion, an oral dosage form of floating gellan beads containing AHA may form a useful stomach site specific drug delivery system for the treatment of H. pylori infection.
Keywords: Acetohydroxamic acid; Controlled release; Floating drug delivery; Gellan beads; Helicobacter pylori; Stomach-specific delivery